IMF Staff papers : Volume 14 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1967)
This chapter highlights asymmetries and errors in reported balance of payments statistics. The aggregation of individual countries' balance of payments statements into group statements or a world total provides clues to certain inconsistencies and asymmetries present in the figures. The method, however, does not necessarily disclose all the differences and inaccuracies that exist, nor does it clearly indicate generally which figures, by country or by category of transaction, are to be regarded as the more reliable when substantial differences come to light. The IMF staff, working with the national compilers to improve the statistics, has concentrated on producing a record of individual countries' economic transactions with the rest of the world that can be used as a basis for gauging the impact of these transactions on the countries' domestic economy and foreign position. Most of the available balance of payments statistics may be judged reasonably adequate to serve this purpose.